Single molecule magnet with an unpaired electron trapped between two lanthanide ions inside a fullerene - Fupin Liu (Nature Portfolio, 2017)
Single molecule magnets have demonstrated promise for information storage, molecular spintronics and quantum computing, but are limited by their low operational temperatures. Here, Popov and coworkers prepare a SMM with a high blocking temperature of 18 K by trapping two lanthanide ions with a single-electron bond inside a fullerene.